2020
DOI: 10.1002/dc.24530
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of MCM5 (ADXBLADDER) analysis in urine of men evaluated for the initial diagnosis of bladder cancer: A comparative prospective study

Abstract: Background: To compare predictive value of MCM5 to urinary cytology (UC) for the primary diagnosis of bladder cancer (BCa). Methods: We prospectively enrolled 91 patients who presented macroscopic hematuria or persistent lower urinary tract symptoms at our institution. Single voided midstream urine specimens were collected for UC and MCM5 (ADXBLADDER; Arquer Diagnostics Ltd, Sunderland, United Kingdom) assessment. Cystoscopy was used as confirmatory test, and positive cases underwent transurethral resection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Seven studies reported on the diagnostic values of the novel UBTs for the detection of NMIBC during initial diagnosis [34,[39][40][41][42][43][44]. Table 2 summarizes the characteristics of included studies and their main outcomes.…”
Section: Performance In Primary Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies reported on the diagnostic values of the novel UBTs for the detection of NMIBC during initial diagnosis [34,[39][40][41][42][43][44]. Table 2 summarizes the characteristics of included studies and their main outcomes.…”
Section: Performance In Primary Diagnosismentioning
confidence: 99%
“…In terms of Sp, the Xpert bladder cancer test had the highest estimates of 90% in patients with hematuria [40]; in the overall population, it ranged from 77% [40] to 84% [39]. The ADXBLADDER test demonstrated Se up to 87% in patients diagnosed with HG NMIBC, compared with 48-55% in patients diagnosed with LG tumors [41,42]. Similarly, Cxbladder (mix of Triage and Detect) reached the highest Se value of 97% in patients with HG tumors [43,44].…”
Section: Performance In Primary Diagnosismentioning
confidence: 99%
“…In our study, by replacing the UC with Xpert BC Monitor performed over time, we could have avoided up to 73%, 86.2%, or even up to all unnecessary cystoscopies, depending on whether the patient had two, three, or four consecutive negative tests. The panorama of emerging urinary biomarkers in the diagnosis and surveillance of NMIBC is wide, but none are currently included in daily clinical practice probably due to the availability, the cost that limits their use (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, XPERT test with two negative tests avoids nearly 75% of unnecessary cystoscopies [ 229 , 230 , 231 , 232 , 233 , 234 ]. ADXBLADDER™ test measures the expression of MCM5 transcript [ 235 , 236 , 237 ]. In a large blinded prospective study ADXBLADDER™ test had an overall sensitivity of 44% but was able to exclude the presence of the most aggressive tumors with a negative predictive value of 99%.…”
Section: Ease Of Developing Urine Biomarkersmentioning
confidence: 99%
“…In a large blinded prospective study ADXBLADDER™ test had an overall sensitivity of 44% but was able to exclude the presence of the most aggressive tumors with a negative predictive value of 99%. In another study, the test’s sensitivity was lower than urine cytology [ 235 , 237 ].…”
Section: Ease Of Developing Urine Biomarkersmentioning
confidence: 99%